Dinar dan Dirham Sebagai Alternatif Mata Uang: Sebuah Tinjauan Literatur - Noviyanti, Ririn (FALAH Jurnal Ekonomi Syariah, 2017)
The issue of justice becomes a serious problem because of the lack of attention to the current system of justice. In the end, many of the economic actors are realizing that the current system is not capable of delivering optimal results. Various attempts were made to optimize the results but the results were in vain. Various policies have been made to provide solutions to the existing problems, but still unable to prevent the various economic crises that occur in the current system. This study aims to conduct in-depth discussion of the dinar and dirham as an alternative to the world currency solutions using literature approach. Based on the exposure, it can be concluded that dinar and dirham can and can be a solution of the international monetary system and replace the current monetary system. It is therefore ideal for all Muslim countries to embark on the implementation of the Islamic monetary system using dinar and dirham.